Vitamin K1 As A Potential Molecule For Reducing Single-Walled Carbon Nanotubes-Stimulated α-Synuclein Structural Changes And Cytotoxicity - Naskhi, Amitis (Int J Nanomedicine, 2019)
AIMS: Different kinds of vitamins can be used as promising candidates to mitigate the structural changes of proteins and associated cytotoxicity stimulated by NPs. Therefore, the structural changes of α-syn molecules and their associated cytotoxicity in the presence of SWCNTs either alone or co-incubated with vitamin K1 were studied by spectroscopic, bioinformatical, and cellular assays. METHODS: Intrinsic and ThT fluorescence, CD, and Congo red absorption spectroscopic approaches as well as TEM investigation, molecular docking, and molecular dynamics were used to explore the protective effect of vitamin K1 on the structural changes of α-syn induced by SWCNTs. The cytotoxicity of α-syn/SWCNTs co-incubated with vitamin K1 against SH-SY5Y cells was also carried out by MTT, LDH, and caspase-3 assays. RESULTS: Fluorescence spectroscopy showed that vitamin K1 has a significant effect in reducing SWCNT-induced fluorescence quenching and aggregation of α- syn. CD, Congo red adsorption, and TEM investigations determined that co-incubation of α- syn with vitamin K1 inhibited the propensity of α-syn into the structural changes and amorphous aggregation in the presence of SWCNT. Docking studies determined the occupation of preferred docked site of SWCNT by vitamin K1 on α- syn conformation. A molecular dynamics study also showed that vitamin K1 reduced the structural changes of α- syn induced by SWCNT. Cellular data exhibited that the cytotoxicity of α- syn co-incubated with vitamin K1 in the presence of SWCNTs is less than the outcomes obtained in the absence of the vitamin K1. CONCLUSION: It may be concluded that vitamin K1 decreases the propensity of α- syn aggregation in the presence of SWCNTs and induction of cytotoxicity.